QUALITY OF LIFE IN PATIENTS WITH INTERSTITIAL LUNG DISEASE AT THE NATIONAL LUNG HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the quality of life of patients with interstitial lung disease at the National Lung Hospital.Methodology: A cross-sectional descriptive study was conducted on 124 patients diagnosed with interstitial lung disease and treated at the National Lung Hospital from September to December 2024. The assessment tools included the EQ-5D-5L quality of life questionnaire and the VAS.Results: The age group from 61 to 70 years had the highest proportion (40.3%), while the 30 to 40 years group had the lowest (6.5%). The mean age of the patients was 61.1 years. Female patients were predominant, accounting for 66.1%. Regarding the aspects of quality of life assessed by the EQ-5D-5L: 55.6% of patients were affected in their mobility, 41.1% needed assistance with self-care, 53.2% were affected in their usual activities, 52.4% felt pain/discomfort, and 49.2% experienced anxiety/depression. The patients’ quality of life was reduced, with a mean score of 0.8065. The quality of life scores for the different aspects were directly proportional to the SpO2 index and inversely proportional to the mMRC score.Conclusion: The quality of life of patients with interstitial lung disease at the National Lung Hospital is reduced, particularly in the physical and mental aspects. This reduction is closely related to respiratory function indicators such as SpO2 and mMRC. The study’s results suggest that early detection and intervention can improve the patients’ quality of life.
Keywords: Interstitial lung disease, quality of life, EQ-5D-5L, EQ-VAS.